The Using Context, Input, Process, and Product Evaluation Model for Evaluating Online College EFL Learning - Jaya, Sinarman; Hamzah, Syukri (International Journal of Educational Research & Social Sciences, 2022)
This research attempts to evaluate the effectiveness of online learning at English Education Study of Muhammadiyah University Bengkulu for period 2020-2021 using context, input, process, and product (CIPP) evaluation model. This qualitative research design uses descriptive evaluative. The data collection instrument used closed questionnaire, structured interviews, and documentation. The data processing techniques refers to the Guttman’s Scale. The result indicated the average value of the context evaluation aspects (0.89), input (0.80), and process evaluation (0.82) and product evaluation (0.85). Thus, it can be concluded that online learning program is appropriate and effective.